Margaret Laurence’s A Jest of God as a Work of Simultaneous Narration - Duncan, Isla (Studies in Canadian Literature, 2008)
Critical reception of Margaret Laurence’s narrative technique in A Jest of God (1966) has been divided, centring on the present-tense, first-person point of view of protagonist Rachel Cameron. Advances in narratological theory since the novel’s publication – especially Dorrit Cohn’s conceptualization of simultaneous narration – facilitates a more refined study. Simultaneous narration combines the mimeticism of first-person fiction and the diegetic norms of verisimilar psychological presentation that mark the tradition of third-person realist fiction. The use of simultaneous narration, along with the creation of what Mikhail Bakhtin calls "true polyphony," reveals Laurence’s novel as narratologically forward-looking.